The Laccase from Micromonospora sp.044 30-1 as a biocatalyst for synthesis of antioxidant compounds - Goodwin, Candice Michelle (Centre for Bioprocess Engineering Research, 2014)
Laccases (EC 1.10.3.2) are blue multicopper oxidases that catalyse a single electron oxidation of various phenolic substrates with an associated four-electron reduction of dioxygen to water. The varied uses of laccase as a biocatalyst can be attributed to its ability to produce a free radical from a suitable substrate. Of importance to the pharmaceutical, chemical, and industrial sectors, are the laccase-catalysed reactions providing means for the synthesis of dimeric phenolics showing biological activity, including antioxidant activity. The objective of this research was to investigate the production of value-added compounds, with biological activity, via laccase-catalysed oxidation reactions. Our laboratory has access to several unique and previously unexploited culture collections obtained from extreme environments spanning the globe. Potentially novel strains were screened for the ability to produce laccases: 14 environmental isolates, of which 2 strains were fungi, 7 were streptomycetes, and 5 were non-streptomycetes, representing the rare actinomycete genera Gordonia, Rhodococcus, Mycobacterium, Amycolatopsis, and Micromonospora were screened. This is the first report of laccase production in these species. A screening protocol, using criteria specifically suited to bioprocess development, was developed to investigate variables affecting the production of laccase by the native strains. Variables investigated included different types of media (nutritional variables), pH, temperature, incubation times, aeration and agitation, salt concentrations, and the effect of inducers on laccase production by the native strains. Of the isolates investigated, actinomycete strain Micromonospora sp. 044 30-1 showed the greatest potential for the production of laccase. This strain may be novel and the role of laccase in this strain may be related to sporulation. Various growth requirements were investigated in order to optimise for maximal laccase production by strain 044 30-1. The optimal medium for laccase production was M172F medium, pH 5, supplemented with a high concentration of Cu2+ (8 mM), and 2.0% sodium chloride. Extracellular laccase production was higher than intracellular laccase production. The successful application of a Micromonospora strain in an airlift bioreactor specifically for the synthesis of laccase was demonstrated. The biocatalytic potential of the laccase from Micromonospora sp. 044 30-1 was investigated. Laccases are responsible for the formation of radicals that can react non-enzymatically with each other to form dimers or oligomers linked by C-C or C-O bonds. This study reports on laccasecatalysed oxidative reactions involving, primarily, tyrosol, monoacetyltyrosol, and to a lesser extent, reactions with totarol, 3-hydroxyanthranilic acid, and 8-hydroxyquinoline. This study reports for the first time the isolation and structure determination of novel biocatalysis reaction products, specifically the dimeric products obtained through biocatalytic reaction of monoacetyltyrosol with Trametes versicolor laccase, and Micromonospora sp. 044 30-1 laccase. The biocatalysis reaction products of the laccase-catalysed oxidation of tyrosol and monoacetylated tyrosol showed higher antioxidant activity than the parent compounds, as determined by the 2,2- diphenyl-1-picrylhydrazyl (DPPH) and low density lipoprotein (LDL) assays, showing that the dimeric derivatives of laccase-catalysed reactions with phenolic compounds have enhanced antioxidant capabilities. The biocatalysis products were also evaluated as antimicrobials and showed antimicrobial activity against E. coli, a vancomycin resistant clinical strain of Enterococcus faecium, a clinically relevant strain of Micrococcus, and Mycobacterium aurum, a strain that displays a similar antibiotic susceptibility profile to Mycobacterium tuberculosis, the causative agent of the prevalent disease tuberculosis.